Conditions of Sericulture Climate Typology in Soppeng District, South Sulawesi, Indonesia - Halide, Lutfi; Sirajuddin, Sitti Nurani; Demmalinno, Eymal B.; Sadapotto, Andi; Ashar, Nurul Magfirah (Agro Bali : Agricultural Journal, 2025)
Sericulture requires a special typology, and it is important to pay attention to it because certain climatic conditions are considered. This research focuses on the climate typology of mulberry cultivation and silkworm cultivation in Soppeng Regency, which can support the sustainability of local sericulture. The research was conducted in the Soppeng Regency between October and December 2023. The data used was primary data originating from in-depth interviews with informants and also secondary data in the form of rainfall, temperature, humidity, etc. obtained from Portal National Aeronautics and Space Administration (NASA) which can be accessed through the site https://power.larc.nasa.gov/data-access-viewer/, Meteorology, Climatology and Geophysics Agency (BMKG) accessed via the page https://www.bmkg.go.id/ And World Meteorological Organization (WMO) through the site https://library.wmo.int/idurl/4/69061 and processed using descriptive techniques. The research results showed that the land area of Soppeng Regency is ± 700 km2, at an average height of ± 60 meters above sea level, and temperature conditions range from 20.5-34.6 degrees Celsius, with air pressure between 1,003.6-1,014.3 millibars, while maximum rainfall is 982.1 mm. In addition to the condition of human resources, silk farmers have in-depth experience with silk cultivation. Thus, this typology supports the sustainability and success of the development of sericulture in the Soppeng Regency.